2002
DOI: 10.1002/etc.5620211205
|View full text |Cite
|
Sign up to set email alerts
|

Using the dioxin receptor–calux in vitro bioassay to screen marine harbor sediments for compounds with a dioxin‐like mode of action

Abstract: The presence of dioxin-like compounds in sediments from harbors and reference sites along the Dutch coast was investigated using the dioxin receptor-chemically activated luciferase gene expression (DR-CALUX) bioassay. The DR-CALUX response varied between 0.2 and 136 ng/kg dry weight expressed in units of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) toxic equivalency quotients (TEQ). The highest CALUX-TEQ values (> 50 ng TEQ/kg dry wt) were found in sediments from the center of the Port of Rotterdam and from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…There were no great differences between the EROD values among the ten sediment samples, indicating that AhR agonists were distributed rather homogeneously in TGR from Wanzhou to the great dam. The determined EROD TCDD EQ (bio-TEQ) amounts in the present study are comparable with ERODinducing potentials of sediments reported by some other studies, including sediments collected from harbors along the Dutch coast ranging from 0.2 to 136 pg TCDD EQ g −1 dw (Stronkhorst et al 2002) and from Osaka Bay, Japan with 3.7 to 140 pg TCDD g −1 dw (Takigami et al 2005) tested with H4IIE-luc hepatoma cell line after 24 h of exposure, as well as sediments collected from Wenyu River, China with 15 to 64 pg TCDD g −1 tested with H4IIE hepatoma cell line after 72 h of exposure (Luo et al 2009) and from Yeongil Bay, Korea ranging from 2.8 to 320 pg TCDD g −1 dw tested with H4IIE-luc hepatoma cell line after 72 h of exposure (Koh et al 2006). On the other hand, the EROD bio-TEQ amounts reported in our study are higher than those reported in sediments from west coast of South Korea with non-detectable to 11 pg TCDD g −1 dw and north coast of Bohai Sea, China with nondetectable to 28 pg TCDD g −1 dw (Hong et al 2012) and sediments from Meiliang Bay, Lake Taihu before the ecological remediation project ranging from 17.8 to 38.5 pg TCDD g −1 dw (Qiao et al 2009) which were all tested with H4IIE rat hepatoma cells after 72 h of exposure.…”
Section: Erod Activity Of Samplessupporting
confidence: 91%
“…There were no great differences between the EROD values among the ten sediment samples, indicating that AhR agonists were distributed rather homogeneously in TGR from Wanzhou to the great dam. The determined EROD TCDD EQ (bio-TEQ) amounts in the present study are comparable with ERODinducing potentials of sediments reported by some other studies, including sediments collected from harbors along the Dutch coast ranging from 0.2 to 136 pg TCDD EQ g −1 dw (Stronkhorst et al 2002) and from Osaka Bay, Japan with 3.7 to 140 pg TCDD g −1 dw (Takigami et al 2005) tested with H4IIE-luc hepatoma cell line after 24 h of exposure, as well as sediments collected from Wenyu River, China with 15 to 64 pg TCDD g −1 tested with H4IIE hepatoma cell line after 72 h of exposure (Luo et al 2009) and from Yeongil Bay, Korea ranging from 2.8 to 320 pg TCDD g −1 dw tested with H4IIE-luc hepatoma cell line after 72 h of exposure (Koh et al 2006). On the other hand, the EROD bio-TEQ amounts reported in our study are higher than those reported in sediments from west coast of South Korea with non-detectable to 11 pg TCDD g −1 dw and north coast of Bohai Sea, China with nondetectable to 28 pg TCDD g −1 dw (Hong et al 2012) and sediments from Meiliang Bay, Lake Taihu before the ecological remediation project ranging from 17.8 to 38.5 pg TCDD g −1 dw (Qiao et al 2009) which were all tested with H4IIE rat hepatoma cells after 72 h of exposure.…”
Section: Erod Activity Of Samplessupporting
confidence: 91%
“…In past years, ER-Luc, YES and YAS have been routinely used to determine (anti) estrogenic or (anti) androgenic activity in complex field samples including extracts of water, production water, suspended particulate matter, sediment and fish bile (Garcia-Reyero et al, 2001;Murk et al, 2002;Legler et al, 2002aLegler et al, , 2002bThange et al, 2000;Houtman et al, 2004;Thomas et al, 2006;Johnston et al, 2007). The methods for conducting ER-Luc, YES and YAS are fully described and validated in the scientific literature (see table below).…”
Section: Progress and Opportunities For In Vitro Bioassays Of Endocrimentioning
confidence: 99%
“…Any risk will be relative to the exposure assumed in the derivation of the guideline and the exposure likely in the actual situation. In some international guidelines concerning the regulation of dioxins, sediments are divided pragmatically into 'clean' and polluted locations on the basis of existing measurements of in vitro bioassays, as with the DR-Luc/DR-CALUX (Stronkhorst et al, 2002). The expected serious chronic effect levels are the average maximum found at locations assumed to be 'clean'.…”
Section: Derivation Of Ac For Dr-lucmentioning
confidence: 99%
See 2 more Smart Citations